Pengaruh RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital) terhadap Financial Distress Perusahaan Perbankan di Indonesia - Soffi Marisha Yuliani; Tantina Haryati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to examine and analyze the effect of RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital) on the financial distress of banking companies in Indonesia. The population used in this study are all banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. This research is a quantitative research. This study uses secondary data used in the form of financial statements and annual reports of banking companies for the period 2017-2021 obtained from the Indonesia Stock Exchange (IDX) website and the official website of banking companies. The sampling technique used purposive sampling method. Based on the criteria or considerations that have been determined, 14 companies were obtained as research samples. The analysis technique in this study uses statistical calculations, using IBM SPSS 22.0 software for windows. The results of this study state that the Risk Profile has a negative effect on Financial Distress. The results of this study state that Good Corporate Governance has a negative effect on Financial Distress. The results of this study indicate that Earnings has a negative effect on Financial Distress. The results of this study indicate that Capital has a positive effect on Financial Distress. Keywords: Risk Profile; Good Corporate Governance; Earnings; Capital; Financial Distress